The development of water house navigation with Garmin handheld global positioning system [electronic resource] - Muhammad Firdaus Aminuddin, 1989- author 638693 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda Kejuruteraan (Geomatik)) - Universiti Teknologi Malaysia, 2013